Barley Nepenthesin-Like Aspartic Protease HvNEP-1 Degrades Fusarium Phytase, Impairs Toxin Production, and Suppresses the Fungal Growth - Bekalu, Zelalem Eshetu; Dionisio, Giuseppe; Madsen, Claus Krogh; Etzerodt, Thomas; Fomsgaard, Inge S.; Brinch-Pedersen, Henrik (Frontiers in Plant Science, 2021)
Nepenthesins are categorized under the subfamily of the nepenthesin-like plant aspartic proteases (PAPs) that form a distinct group of atypical PAPs. The current study describes the effect of nepenthesin 1 (HvNEP-1) protease from barley (Hordeum vulgare L.) on fungal histidine acid phosphatase (HAP) phytase activity. Signal peptide lacking HvNEP-1 was expressed in Pichia pastoris and biochemically characterized. Recombinant HvNEP-1 (rHvNEP-1) strongly inhibited the activity of Aspergillus and Fusarium phytases, enzymes that release inorganic phosphorous from phytic acid. Moreover, rHvNEP-1 suppressed in vitro fungal growth and strongly reduced the production of mycotoxin, 15-acetyldeoxynivalenol (15-ADON), from Fusarium graminearum. qPCR analysis of trichothecene biosynthesis genes (TRI) confirmed that rHvNEP-1 strongly repressed the expression of TRI4, TRI5, TRI6 and TRI12 in F. graminearum. Co-incubation of rHvNEP-1 with recombinant F. graminearum (rFgPHY1) and F. culmorum (FcPHY1) phytases induced substantial degradation of both Fusarium phytases indicating that HvNEP-1 mediated proteolysis of the fungal phytases contributes for the HvNEP-1 based suppression of Fusarium.